Analysis of the deradicalization program in the French Republic - Iličić, Kristina; Toth, Luka (Crisis Management Days, 2024)
In the Republic of France, dealing with the issue of radicalization and deradicalization is relatively recent. In French deradicalization programs, a highly centralized approach was applied with a large role of the government and a very small role of civil society. Also, deradicalization programs are structured and clearly set at the state level. The main aim of this paper is to analyze how the deradicalization programs was thought out and implemented in the Republic of France, as well as the results and success of these programs. It can be concluded that the deradicalization programs in France have their shortcomings and there are no clearly established criteria by which to evaluate the program and, if necessary, modify them to make them more successful. The research methods used in the work are deductive method, analysis method, descriptive method and case study method.